Scientific Circulation, Language Policies, and the Geopolitics of Translation in the IBGE Geographic Bulletin During the Estado Novo Period (1943–1945): an introduction - Guilherme da Silva Ribeiro (Geografares, 2024)
This introductory text seeks to explore the history of geography from a perspective rarely examined in Brazil, both in terms of subject matter and methodology: that of languages and translations, framed by decoloniality and translation studies. To this end, we focus on the IBGE Geographic Bulletin during the Estado Novo period (1943–1945), identifying a noteworthy issue: Implementing an intensive multilingual editorial policy facilitates scientific circulation through various translations. However, this policy emerged within a context where the Estado Novo promoted the Portuguese language as a key symbol of nationalism and national identity. Beyond shedding new light on the history of Brazilian geography, a study of the Geographic Bulletin can contribute to understanding why a peripheral country invests so heavily in translation as a genre of scientific exchange and how this process unfolds.
Keywords: nationalism; multilingualism; translations